2014
DOI: 10.1080/03098265.2014.963527
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of student and faculty mentor perceptions of an international undergraduate research program in physical geography

Abstract: In this study, we assess whether students and their faculty mentors in a Research Experience for Undergraduates program have similar perceptions about the relative importance of different outcomes of their study abroad experience. Results of a Q-analysis reveal a significant difference of opinion between the students and the faculty mentors. It is argued that the faculty mentors need to spend more time in the field with their students and recognize that undergraduate research provides students with skills and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The case studies program had an impact on student choices about their learning, much like the impacts of research-led teaching in universities (Lindsay et al 2002). Focus group participants agreed that the case studies, by presenting interesting research outside the curriculum, influenced students to choose geography as their university subject -a finding which echoes experiences of more intensive programs with smaller cohorts of students where students attend university-organized events (Houser et al 2015). Interestingly, one focus group participant suggested that the research case studies had played a key part in causing at least two students to select the university as their first choice university.…”
Section: The Impacts Of Research-led Teaching In Schoolsmentioning
confidence: 99%
See 3 more Smart Citations
“…The case studies program had an impact on student choices about their learning, much like the impacts of research-led teaching in universities (Lindsay et al 2002). Focus group participants agreed that the case studies, by presenting interesting research outside the curriculum, influenced students to choose geography as their university subject -a finding which echoes experiences of more intensive programs with smaller cohorts of students where students attend university-organized events (Houser et al 2015). Interestingly, one focus group participant suggested that the research case studies had played a key part in causing at least two students to select the university as their first choice university.…”
Section: The Impacts Of Research-led Teaching In Schoolsmentioning
confidence: 99%
“…University lecturers have tended to physically engage with schools through four main mechanisms: delivering lectures and talks to students in their schools (Lynch 2002); delivering lectures to teachers at conferences and seminars promoted by discipline-specific organizations (e.g. in the UK context -the Geographical Association) (Stannard 2003;Yarwood and Davison 2007); hosting students and teachers at university-organized events (Houser et al 2015); and involving students in research projects and internships (Riggs et al 2007). Engagement persists across all four formats, largely driven by aims to improve recruitment, particularly in the North American context where recruitment to bachelor programs is currently problematic (Miller et al 2007;Gonzales et al 2010;Houser et al 2015;Leydon et al 2016).…”
Section: Research-led Teaching and The University-school Dividementioning
confidence: 99%
See 2 more Smart Citations
“…Efforts have been made to support undergraduate participation in research with the expectation that students will benefit from participating in scientific research. Previous reports have focused on case studies from successful experiences or practices from various disciplines in multiple countries (Abdel‐Qader, ; Abudayyeh, ; Cantor, Delauer, Martin, & Rogan, ; Gannon & Maher, ; Karsai, Knisley, Knisley, Yampolsky, & Godbole, ; Prunuske, Wilson, Walls, & Clarke, ; Shah & Bowyer, ; Weigel, ; Yarnal & Neff, ), effects on mentees (undergraduates) and mentors (faculty, post‐doctoral scholars, or graduate students) (Cuthbert, Arunachalam, & Licina, ; Dolan & Johnson, ; Hall & Jaugietis, ; Healey, Jordan, Pell & Short, ; Hunter, ; Lopatto, ; Seymour et al, ), factors (e.g., status, gender, and race) affecting outcomes (Byarswinston, Branchaw, Pfund, Leverett, & Newton, ; Hathaway et al, ; Lopatto, ; Mekolichick & Gibbs, ), evaluation of the role of mentors and mentoring function (Houser, Lemmons, & Cahill, ; Nora & Crisp, ; Weigel, ), and perception of differences between mentees and mentors (Behar‐Horenstein, Roberts, & Dix, ; Houser, Cahill, & Lemmons, ; Kardash and Edwards, ). Most of these studies were based on interviews and surveys.…”
Section: Introductionmentioning
confidence: 99%